Biomedical Waste Management in Nepal: a Review - Chaudhary, Nagendra; Mahato, S. K.; Chaudhary, S.; Bhatiya, B D (Journal of Universal College of Medical Sciences, 2015)
Available with full text. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12070 Journal of Universal College of Medical Sciences (2014) Vol. 02, No. 04, Issue 08 Page : 45-52